Revealing the Simultaneous Effects of Conductivity and Amorphous Nature of Atomic‐Layer‐Deposited Double‐Anion‐Based Zinc Oxysulfide as Superior Anodes in Na‐Ion Batteries. Issue 37 (2nd August 2019) - Sinha, Soumyadeep; Didwal, Pravin N.; Nandi, Dip K.; Verma, Rakesh; Cho, Jae Yu; Kim, Soo‐Hyun; Park, Chan‐Jin; Heo, Jaeyeong
Abstract: Although sodium‐ion batteries (SIBs) are considered promising alternatives to their Li counterparts, they still suffer from challenges like slow kinetics of the sodiation process, large volume change, and inferior cycling stability. On the other hand, the presence of additional reversible conversion reactions makes the metal compounds the preferred anode materials over carbon. However, conductivity and crystallinity of such materials often play the pivotal role in this regard. To address these issues, atomic layer deposited double‐anion‐based ternary zinc oxysulfide (ZnOS) thin films as an anode material in SIBs are reported. Electrochemical studies are carried out with different O/(O+S) ratios, including O‐rich and S‐rich crystalline ZnOS along with the amorphous phase. Amorphous ZnOS with the O/(O+S) ratio of ≈0.4 delivers the most stable and considerably high specific (and volumetric) capacities of 271.9 (≈1315.6 mAh cm −3 ) and 173.1 mAh g −1 (≈837.7 mAh cm −3 ) at the current densities of 500 and 1000 mA g −1, respectively. A dominant capacitive‐controlled contribution of the amorphous ZnOS anode indicates faster electrochemical reaction kinetics. An electrochemical reaction mechanism is also proposed via X‐ray photoelectron spectroscopy analyses. A comparison of the cycling stability further establishes the advantage of this double‐anion‐based material over pristine ZnO and ZnS anodes. Abstract : Double‐anion‐based amorphous zinc oxysulfide (ZnOS) with optimum O/(O+S) ratio is grown by atomic layer deposition and investigated as a superior anode in sodium‐ion batteries. The long cyclic stability with high specific and volumetric capacity is attributed to the amorphous phase and moderate conductivity of the film. The reaction mechanism between ZnOS and Na ions is established with postcycling analyses.